Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1186/1471-213x-10-83
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Thisbe and Pyramus functional domains reveals evidence for cleavage of Drosophila FGFs

Abstract: BackgroundAs important regulators of developmental and adult processes in metazoans, Fibroblast Growth Factor (FGF) proteins are potent signaling molecules whose activities must be tightly regulated. FGFs are known to play diverse roles in many processes, including mesoderm induction, branching morphogenesis, organ formation, wound healing and malignant transformation; yet much more remains to be learned about the mechanisms of regulation used to control FGF activity.ResultsIn this work, we conducted an analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…The Drosophila FGF primary sequence contains an amino-terminal signal peptide, an FGF core domain and a long carboxy-terminal sequence with no significant homologies to other proteins [5]. Cultured cell studies demonstrated that the carboxy-terminal domains of Pyr and Ths are cleaved off suggesting that these FGFs are produced as precursors and that polypeptides containing the FGF core domain are secreted (Figure 3) [52]. The significance of this potential regulatory step is unclear as transgenes expressing carboxy-terminal truncation of Ths and Pyr are functional indicating that cleavage of the carboxy-terminal domain is not a prerequisite for secretion or receptor activation [52,53].…”
Section: The Fgf Signalling Pathway In Drosophilamentioning
confidence: 99%
See 1 more Smart Citation
“…The Drosophila FGF primary sequence contains an amino-terminal signal peptide, an FGF core domain and a long carboxy-terminal sequence with no significant homologies to other proteins [5]. Cultured cell studies demonstrated that the carboxy-terminal domains of Pyr and Ths are cleaved off suggesting that these FGFs are produced as precursors and that polypeptides containing the FGF core domain are secreted (Figure 3) [52]. The significance of this potential regulatory step is unclear as transgenes expressing carboxy-terminal truncation of Ths and Pyr are functional indicating that cleavage of the carboxy-terminal domain is not a prerequisite for secretion or receptor activation [52,53].…”
Section: The Fgf Signalling Pathway In Drosophilamentioning
confidence: 99%
“…Cultured cell studies demonstrated that the carboxy-terminal domains of Pyr and Ths are cleaved off suggesting that these FGFs are produced as precursors and that polypeptides containing the FGF core domain are secreted (Figure 3) [52]. The significance of this potential regulatory step is unclear as transgenes expressing carboxy-terminal truncation of Ths and Pyr are functional indicating that cleavage of the carboxy-terminal domain is not a prerequisite for secretion or receptor activation [52,53]. A case for proteolytic control of FGF ligand distribution has been made during the development of the larval ASP, where spatial restriction of FGF ligands by the extracellular matrix metallo-protease Mmp2 has been shown to concentrate FGF to the tip territory of the air sac by degrading FGF around the adjacent stalk cells [54].…”
Section: The Fgf Signalling Pathway In Drosophilamentioning
confidence: 99%
“…Alternatively, FGFs may exhibit different range of action or be subject to different regulation. Regarding this last point, we have determined that these ligands are differentially cleaved and that the C-terminus of Thisbe may function to inhibit activity 34 . Drosophila, with a total of three FGF ligands compared with 22+ genes in vertebrates, is an attractive model system to investigate the individual activities of FGFs.…”
Section: Distinct and Overlapping Functions Of Fgf Ligandsmentioning
confidence: 99%
“…In particular, our group has demonstrated that Notch loss of function disrupts RBG migration (Shamloula et al, 2002), while exogenous EGF signaling has been shown to activate long-distance migration of retinal progenitor cells (Unachukwu et al, 2013). In addition, FGF ligands are known to control glia differentiation, migration, and axonal wrapping central to vision (Silies et al, 2010; Tulin and Stathopoulos, 2010a,b). FGF signaling molecules are believed to be produced at a localized source and then dispersed into targeted tissue.…”
Section: Introductionmentioning
confidence: 99%